PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN - Melisa Syahnaz; Tubandrijah Herawati (Jurnal Ilmiah Mahasiswa FEB, 2012)
This research is aimed to analyze the influence of corporate social responsibility activities to financial performance on banking companies. ROA, ROE and CAR are used as the proxy of financial performance. Public banking companies which are listed in Indonesia Stock Exchange  year 2009-2011 is used as an object of research. Samples in this research are determined by purposive sampling method. The research data is analyzed by using multiple linear regression.  The result shows that corporate social responsibility has positive effect on ROA and ROE. Meanwhile, corporate social responsibility shows no effect on CAR.  Key Words : Corporate Social Responsibility, Financial Performance, ROA,     ROE, CAR